Interferences of ciberculture in high performance athletes: focus on soccer athletes - Verzani, Renato Henrique (2018)
The convergence of communities in the virtual environment and the increasingly representative immersion in social networks allows an increase of communication, which can be synchronous and asynchronous, and with enormous speed and reach. This potential increases vigilance and vulnerability.The objective was to verify the immersion of athletes in online social networks and possible implications related to this involvement. It can be observed that there is a high involvement of the athletes with the online social networks, not only being present in several of these, but also presenting a high frequency of use. Dividing by levels of expertise, it was found that the smaller ones had a greater numeric tendency to get involved in problems and also as to the use, even though they also presented a higher level of concern with what they post in relation to those with greater expertise. Therefore, it has been proven that there is a high involvement of the athletes with this online context, thus allowing the occurrence of problems involving fans and journalists due to the inherent unpredictability of social networks, requiring the attention of professionals involved with these new demands.